2017
DOI: 10.3389/fpsyg.2017.00733
|View full text |Cite
|
Sign up to set email alerts
|

Arousal in Nocturnal Consciousness: How Dream- and Sleep-Experiences May Inform Us of Poor Sleep Quality, Stress, and Psychopathology

Abstract: The term “sleep experiences,” coined by Watson (2001), denotes an array of unusual nocturnal consciousness phenomena; for example, nightmares, vivid or recurrent dreams, hypnagogic hallucinations, dreams of falling or flying, confusional arousals, and lucid dreams. Excluding the latter, these experiences reflect a single factor of atypical oneiric cognitions (“general sleep experiences”). The current study is an opinionated mini-review on the associations of this factor—measured with the Iowa sleep experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 98 publications
5
43
0
1
Order By: Relevance
“… Watson (2001) construed LD, along with other unusual dream phenomena, as representing nocturnal manifestations of an “unusual cognitions” continuum (e.g., bizarreness, oddity), which during daytime is characterized by schizotypy and dissociative experiences. Notably, LD represents a “mixed state” between waking and sleeping consciousness ( Mahowald and Schenck, 2001 ; Voss et al, 2009 ); other unusual dream phenomena representing mixed sleep-wake states (e.g., nightmares, recurring dreams, vivid dreams, kinesthetic dreams, and hypnagogic hallucinations) have been consistently positively associated with several psychopathological symptoms (such as depression and anxiety), stress, and negative affect, and have been viewed as representing an intrusion of waking arousal into the sleeping consciousness ( Soffer-Dudek and Shahar, 2011 ; Soffer-Dudek, 2017a ). In fact, they seem to be an early marker of covert psychological distress ( Soffer-Dudek and Sadeh, 2013 ; Soffer-Dudek, 2016 ), and may be viewed as an indicator of poor sleep quality ( Soffer-Dudek, 2017a ).…”
Section: Introductionmentioning
confidence: 99%
“… Watson (2001) construed LD, along with other unusual dream phenomena, as representing nocturnal manifestations of an “unusual cognitions” continuum (e.g., bizarreness, oddity), which during daytime is characterized by schizotypy and dissociative experiences. Notably, LD represents a “mixed state” between waking and sleeping consciousness ( Mahowald and Schenck, 2001 ; Voss et al, 2009 ); other unusual dream phenomena representing mixed sleep-wake states (e.g., nightmares, recurring dreams, vivid dreams, kinesthetic dreams, and hypnagogic hallucinations) have been consistently positively associated with several psychopathological symptoms (such as depression and anxiety), stress, and negative affect, and have been viewed as representing an intrusion of waking arousal into the sleeping consciousness ( Soffer-Dudek and Shahar, 2011 ; Soffer-Dudek, 2017a ). In fact, they seem to be an early marker of covert psychological distress ( Soffer-Dudek and Sadeh, 2013 ; Soffer-Dudek, 2016 ), and may be viewed as an indicator of poor sleep quality ( Soffer-Dudek, 2017a ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in recent years it has been reported that an array of unusual dreams, including dreams of flying or falling, vivid dreams, recurring dreams, and dreams of dying, are components of a construct labeled “sleep experiences” ( Watson, 2001 ). This construct is closely related to psychological symptoms and stress ( Soffer-Dudek, 2017 ). TD have also been directly related to psychopathology ( Coolidge and Bracken, 1984 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sufficient good sleep quality and sleep hygiene are crucial for mental and physical health (e.g., Benca et al, 1992;Kahn-Greene et al, 2007;Cappuccio et al, 2010). In addition to insufficient or poor sleep, unusual dreaming may also be considered as a form of sleep disruption, when arousal or vigilance permeate nocturnal consciousness (Soffer-Dudek, 2017). LD theoretically also represent arousal within sleep, but they do not show the robust relationships with distress shown by other unusual sleep experiences (Soffer-Dudek, 2017).…”
mentioning
confidence: 99%
“…In addition to insufficient or poor sleep, unusual dreaming may also be considered as a form of sleep disruption, when arousal or vigilance permeate nocturnal consciousness (Soffer-Dudek, 2017). LD theoretically also represent arousal within sleep, but they do not show the robust relationships with distress shown by other unusual sleep experiences (Soffer-Dudek, 2017). However, that conclusion was based mostly on studies that assessed LD by averaging dream awareness with dream control into a single measure.…”
mentioning
confidence: 99%
See 1 more Smart Citation